(untitled) (Revista Direito em Debate, 2020)
From a look at the advances that technology has brought in the workplace and its relationships in the environment, this study aims to address the evolution of work processes from the conception of uberization in labor law. Based on the basic theory of historical materialism developed by Karl Marx, it has been proved that the exploitation of man’s labor force has become more present than ever before, in which the advances of the capitalist system through the uberization of labor processes, lead workers to use mainly computer resources in industrial relations. The method used for the work consisted of the hypothetical deductive. It remains proven that work processes have become uberized, where new forms of work are developed largely on digital platforms and for a period of time. As the use of technological instruments has become indispensable for most work processes, the reflections, on the other hand, affect workers’ health due to competition and the demand for better production results. Similarly, it was observed that work processes became more autonomous and self-managed, changing the traditional structure of employment and subordination.